The Implementation of Visual, Auditory, Kinesthetic (VAK) Learning Model in Improving Students’ Achievement in Writing Descriptive Texts - Oki Dwi Ramadian; Bambang Yudi Cahyono; Nunung Suryati (English Language Teaching Educational Journal, 2019)
The English teaching in a public vocational school of Akomodasi Perhotelan (SMK AP) so far has shown unsatisfactory result. Based on the preliminary study it was found that the writing skill of the tent graders of SMK AP 3 was low. This classroom action research was aimed at improving the students’ writing skill of descriptive text by implementing VAK learning model. In this study 26 students were selected as subjects. This study was completed through one cycle using VAK learning model. The findings revealed that students’ writing scores increased after the researcher implemented the VAK learning model. The average score of the students improved 38.18 points into 81.49 compared to their scores in the preliminary study which was 43.31. Out of 26 students, there were only 7 (26.92%) who failed to achieve the minimum mastery criteria (KKM). It can be inferred from the findings that the VAK learning model succeeded in helping the students to improve their writing’ achievement. The result of this study implies that VAK learning model can be an alternative to improve the students’ writing skill.